2007
DOI: 10.1021/nl071964s
|View full text |Cite
|
Sign up to set email alerts
|

An Electrothermal Carbon Nanotube Gas Sensor

Abstract: We show both gas pressure and species sensing capabilities based on the electrothermal effect of a multiwalled carbon nanotube (MWCNT). Upon exposure to gaseous environments, the resistance of a heated MWCNT is found to change following the conductive heat-transfer variances of gas molecules. To realize this mechanism, a suspended MWCNT is constructed by synthesis and assembly in localized chemical vapor deposition that is accomplished within seconds via real-time electrical feedback control. Vacuum pressure s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
96
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(98 citation statements)
references
References 25 publications
2
96
0
Order By: Relevance
“…Gas monitoring represents a growing demand driven by their applications in air quality control, environmental protection and healthcare as well as security [1][2][3][4][5]. Recently, sensitive gas sensors based on semiconductor oxides gain special interest due to their good reproducibility, compact size, ease of use, and low cost [6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Gas monitoring represents a growing demand driven by their applications in air quality control, environmental protection and healthcare as well as security [1][2][3][4][5]. Recently, sensitive gas sensors based on semiconductor oxides gain special interest due to their good reproducibility, compact size, ease of use, and low cost [6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Kaul, 2009). A recent article by Kawano (Kawano et al, 2007) presents a sensing mechanism similar to that reported here, which utilized MWNTs grown using a localized synthesis process (Kawano et al, 2006). Here we report on the device application of sensors based on SWNTs that were grown using conventional thermal CVD.…”
Section: Application In Pressure Sensorsmentioning
confidence: 71%
“…Further, when a gas is injected in the vacuum chamber, fast CNTs cooling by the gas may result in a measurable current increase. This effect was first observed by Kawano et al, 2007. For suspended nanotubes (and attached nanoparticles), heating by Joule effect is much stronger, resulting in strong enhancement of chemical sensitivity to gas (oxygen).…”
Section: Mwcnts For Sensing Applicationsmentioning
confidence: 88%
“…The electrothermal mechanism is due to changes of the CNT electrical resistance (Kuo et al, 2007). Metallic MWCNTs can be self-heated considerably by current (in the way similar to NWs), and this leads to a rise of resistivity, with the temperature coefficient of resistivity (TCR) ~ 0.1% o C -1 (Kawano et al, 2007). Further, when a gas is injected in the vacuum chamber, fast CNTs cooling by the gas may result in a measurable current increase.…”
Section: Mwcnts For Sensing Applicationsmentioning
confidence: 99%